Distribution of Inheritance According to Mawaris Islamic Jurisprudence Law in the Compilation of Islamic Law - Muhammad Adam Surya Raya; Salmawati Salmawati; Mursyid Mursyid (Faculty of Law, Universitas Muslim Indonesia, 2025)
Abstract: The application of the reverse burden of proof in gratification cases within corruption offenses is a pivotal legal instrument in Indonesia’s anti-corruption strategy, yet its effectiveness remains subject to both theoretical debate and practical challenges. While this mechanism normatively grants defendants the opportunity to prove that the gratification received is unrelated to their official position, there is a notable research gap in examining how judicial reasoning determines the success or failure of such proof in court proceedings. This study employs a normative juridical method with a case study approach, focusing on court decisions that implement the reverse burden of proof. The analysis centers on the construction of judicial arguments in assessing the evidence and statements presented by the defendant. The findings reveal that the defendant failed to convince the panel of judges that the gratification in question was beyond the scope of their authority, highlighting the substantial evidentiary burden borne by defendants. These results underscore the necessity for a comprehensive understanding of both substantive and procedural legal aspects in reverse proof mechanisms, while contributing to the broader discourse on the development of criminal procedural law in corruption cases in Indonesia.